Akad Wakalah bil Ujroh sebagai Solusi Transaksi Bisnis di Era Digital - Sholihah, Nurlailiyah Aidatus; Suhendar, Fikry Ramadhan; Caswati, Caswati (International Conference on Islamic Economic (ICIE), 2023)
This article aims to analyze the urgency of the wakalah bil ujroh contract in business transactions in the digital era. The research method in this article uses a qualitative method with literature study as the approach. The data source is in the form of library publications. The type of data is in the form of written narratives or documents contained in publication sources. Data collection techniques are carried out by tracking the sources of these publications. The data analysis technique is descriptive. Based on the research conducted, it was found that the wakalah bil ujroh contract can be one of the contracts used in business transactions in the digital era. This is because the use of the contract can prevent business transactions from elements that contain usury and garar. Wakalah bil ujroh contract is a representative contract made by a person to another person to carry out an action or transaction accompanied by a reward for the action or transaction. Based on this understanding, rewards that are included with payments for a transaction or reward for a need are allowed in Islamic economics and are not included as riba but as wages or ujroh.